Eucheuma Cottonii Hydrochar: A Promising Adsorbent for Congo Red Dye - Putri, Bunga Indah; Arsyad, Fitri Suryani; Hanifah, Yulizah; Ahmad, Nur (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2025)
This study investigates the transformation of Eucheuma cottonii (EC) into a highly efficient adsorbent through hydrothermal carbonization at 200°C, resulting in hydrochar (HC-200). The FT-IR analysis reveals significant structural changes, including reduced intensity of oxygenated functional groups such as carbonyl and hydroxyl, alongside increased aromaticity, contributing to enhanced hydrophobicity and structural stability. These alterations render HC-200 well-suited for adsorption applications. BET analysis highlights a marked increase in the specific surface area and mesoporosity of HC-200 compared to EC, with hysteresis loops confirming enhanced adsorption capacity. SEM imaging shows substantial morphological changes, including rougher surfaces, increased porosity, and the presence of spheroidal structures, indicative of successful carbonization and improved diffusivity. Adsorption studies underline HC-200's superior performance in anionic dye removal, with a maximum adsorption capacity 37.894 mg/g. pHpzc analysis demonstrates more acidic surface characteristics, which favor adsorption in acidic conditions. Adsorption kinetics align predominantly with the pseudo-second-order model, indicating chemisorption as the dominant mechanism. The regeneration study shows HC-200's excellent reusability, maintaining significant adsorption efficiency over seven cycles, whereas EC experiences a steep decline in performance.